2016
DOI: 10.1016/j.cortex.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Internal modeling of upcoming speech: A causal role of the right posterior cerebellum in non-motor aspects of language production

Abstract: Some language processing theories propose that, just as for other somatic actions, self-monitoring of language production is achieved through internal modeling. The cerebellum is the proposed center of such internal modeling in motor control, and the right cerebellum has been linked to an increasing number of language functions, including predictive processing during comprehension.Relating these findings, we tested whether the right posterior cerebellum has a causal role for self-monitoring of speech errors. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 62 publications
7
30
0
Order By: Relevance
“…We have shown previously that low-frequency right cerebellar rTMS disrupts the prediction of upcoming sentence content in a language comprehension task (Lesage et al, 2012), a finding that we replicated recently using cathodal tDCS (Miall et al, 2016). In the language production domain, rTMS over right, but not left, cerebellum impairs higher level speech monitoring, including internal prediction of upcoming speech (Runnqvist et al, 2016), and a recent study found that right cerebellar tDCS improved performance in a sentence completion task (D'Mello et al, 2017). Such neurostimulation evidence dovetails nicely with the present data to show that the right posterior cerebellum is causally involved in linguistic prediction to aid both language comprehension and language production.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that low-frequency right cerebellar rTMS disrupts the prediction of upcoming sentence content in a language comprehension task (Lesage et al, 2012), a finding that we replicated recently using cathodal tDCS (Miall et al, 2016). In the language production domain, rTMS over right, but not left, cerebellum impairs higher level speech monitoring, including internal prediction of upcoming speech (Runnqvist et al, 2016), and a recent study found that right cerebellar tDCS improved performance in a sentence completion task (D'Mello et al, 2017). Such neurostimulation evidence dovetails nicely with the present data to show that the right posterior cerebellum is causally involved in linguistic prediction to aid both language comprehension and language production.…”
Section: Discussionmentioning
confidence: 99%
“…Inner speech as an error monitoring system has been hypothesized as part of the language system (Bredart, 1991;G. S. Dell & Repka, 1992;Hartsuiker & Kolk, 2001;MacKay, 1992;Motley, Camden, & Baars, 1982;Runnqvist et al, 2016;van Wijk & Kempen, 1987;Vigliocco & Hartsuiker, 2002). Inner speech, in these models, serves as an internal 'buffer' for possible language errors.…”
Section: Discussionmentioning
confidence: 99%
“…(4) The stimuli were either categories or letters (for the verbal fluency tasks), or pictures triggering single-word utterances (i.e., nouns or verbs, for picture-naming tasks). Studies using printed words as stimuli were omitted in order to avoid potential confounds with reading ability (Cappelletti, Fregni, Shapiro, Pascual-Leone, & Caramazza, 2008;Nozari & Thompson-Schill, 2013;Pope & Miall, 2012;Runnqvist et al, 2016;Shapiro et al, 2001;Spielmann et al, 2017;Tremblay & Gracco, 2009), as were studies that required the production of multiword utterances (Arnold & Nozari, 2017;Nozari, Arnold, & Thompson-Schill, 2014) or in which a mixture of verbal fluency and picture naming was used (Jeon & Han, 2012);…”
Section: Study Selection and Analysismentioning
confidence: 99%